Clipped Wings and the Great Abyss: Cognitive Stylistics and Implicatures in Abiezer Coppe’s ‘Prophetic’ Recantation - Borgogni, Daniele (Studia Anglica Posnaniensia, 2017)
In this article, two major paradigms within cognitive stylistics, the Conceptual Metaphor Theory (CMT) and the Conceptual Integration Theory (CIT), are applied as largely complementary approaches to discuss the scope and implicatures of the central metaphorical image of Copp’s Return to the wayes of Truth (1651), a text written by one of the most famous radical preachers of the Civil War period as a plea to be released from prison. The article will focus on how the linguistic and cultural contexts of Coppe’s prophetic writing, in their interaction with the dynamic conceptual relationships of a conceptual integration network, open up new possibilities of perspectivizing and insinuating radically different meanings and implicatures: the use of blends in Coppe’s text has a direct effect on the structure of the analogies that can be made between mental spaces, thereby triggering new meaning effects, supplementary symbolizing patterns, and unpredictable perlocutionary effects.